Kajian Model Pembelajaran Word Square terhadap Pembelajaran Bahasa di Sekolah - Hesty Kusumawati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research examines the word square learning model of Language learning. The goal is to describe the influence and effectiveness of using this model on Language learning so that it becomes an alternative for educators to use this model. This research uses a literature study with a descriptive qualitative approach because this research uses google scholar indexed journals as a data source. In the process of data analysis, researchers only take data from journals in the last 5 years, namely 2019-2023. In this study, 14 reputable journals were obtained with the application of the word square model to various types of language learning, namely Indonesian, English, German, Japanese and French. This research also discusses the impact of this learning model, which has an impact on vocabulary mastery, reading comprehension, learning outcomes, and speaking skills.